Mismatch Amplification Mutation Assays of Chikungunya Virus and O'nyong-Nyong Virus; A Simple and Reliable Method for Surveillance and Identification of Emerging Alphaviruses - Lwande, Olivia Wesula; Luande, Verah Nafula; Pereira de Freitas, Amanda; Tajedin, Leila; Ahlm, Clas; Näslund, Jonas; Evander, Magnus; Bucht, Göran (Frontiers in Virology, 2022)
The mosquito-borne alphaviruses chikungunya virus (CHIKV) and o’nyong-nyong virus (ONNV) are closely related and belong to the Semliki forest virus serocomplex. The two viruses are associated with large outbreaks with significant morbidity. However, they are transmitted by different mosquito vectors and accordingly need different prevention strategies. The viruses are difficult to distinguish clinically and there is lack of sensitive and specific assays that can discriminate CHIKV and ONNV. Therefore, there is a need for new methods that may determine the true burden of the diseases caused by these viruses, especially in resource-poor settings. To distinguish between CHIKV and ONNV, we designed and optimized genetic methods referred as Melt Analysis of Mismatch Amplification Mutation Assay (Melt-MAMA) and Agarose gel-based Mismatch Amplification Mutation Assay (Agarose-MAMA). The identification is based on nucleotide polymorphism using two competing forward primers and a common reverse primer that target selected sites in the envelope genes (E1 and E2). A specific shift in the melting point and mobility on agarose gels is obtained by tailing one of the two competing primers with a stretch of G/C rich nucleotides. The melting point analysis by Real-Time PCR (Melt-MAMA) or gel-shift assay (Agarose-MAMA assay) for CHIKV and ONNV were found reproducible and the sensitivity of the two assays was estimated to less than 100 template copies/reaction. Furthermore, no cross-reactivity to related viruses of the same serocomplex such as Mayaro virus, Ross River virus or Semliki forest virus, or to Sindbis virus that belong to the Western Equine Encephalitis Virus serocomplex or to unrelated viruses such as Flavivirus (West Nile virus and dengue virus) and Orthobunyavirus (Inkoo virus and Tahyna virus). The results from the two assays were comparable when the obtained amplicons are analyzed by Melt-MAMA or by Agarose-MAMA. Herein we present, reliable and robust methods that can discriminate between CHIKV and ONNV. The methods are valuable in well-equipped laboratories, in basic clinical settings (e.g. in developing countries) as well as in field situations. The approach may also be applicable in the distinction of other closely mosquito-borne viruses that belong to the same serogroup.